Pengaruh suhu dan lama penyimpanan terhadap antioksidan ASI - Enggar; Margareta Paula Klara (MEDIA ILMU KESEHATAN, 2021)
Background: Breast milk contains antioxidants that can inhibit oxidative stress in infants. Milking is now a much-done option. Breast milk is stored so that the baby can drink it at any time. The presence of temperature treatment and long storage of breast milk triggers physical and chemical changes, one of which is antioxidants that babies desperately need to combat the effects of free radicals.Objective: The research aimed at comparing antioxidants in the fresh breast milk and storage breast milk.Methods: This was the true experimental research. Samples were taken using the purposive sampling technique of 24 samples. The breast milk was tested its antioxidant content using DPPH, initial control, and giving two treatment factors. The first treatment was the breast milk storage at room temperature (fresh breast milk), refrigerator temperature, and freezer temperature. The second treatment was breast milk storage for 7, 14, 30, and 60 days. The data were analyzed using T-Test and repeated Anova.Results: The research result indicates that there is a decrease of the antioxidants between the fresh breast milk and the breast milk stored in the refrigerator temperature of 20C with the storage duration of 7 days, and freezer temperature of -160C with the storage duration 14, 30, and 60 days, p=0.000.Conclusion: The antioxidant is better stored at the temperature of -160C than the temperature of 20C. The longer the storage, the lower the breast milk antioxidant.